High-strength weather-resistant rubber composition, master batch and preparation method

By scientifically combining EVM, SMA and peroxide, high-strength weathering rubber compositions were prepared, which solved the problem of insufficient tensile strength of EVM, achieved higher tensile strength and weathering performance, and broadened the application range.

CN119708684APending Publication Date: 2025-03-28GUANGDONG HINNO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411816870.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The insufficient tensile strength of ethylene-vinyl acetate rubber (EVM) limits its use in certain applications where there are higher requirements for material strength.

Method used

By scientifically comparing ethylene-vinyl acetate rubber (EVM), styrene-maleic anhydride copolymer (SMA) and peroxide, a high-strength weathering rubber composition was prepared, and high-strength weathering rubber masterbatches were prepared by extrusion granulation process.

Benefits of technology

On the basis of maintaining weather resistance, the tensile strength of the material is significantly improved, the application range of EVM is broadened, and the service life and reliability of the product are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-strength weather-resistant rubber composition, a master batch prepared from the high-strength weather-resistant rubber composition and a method for preparing the master batch. The high-strength weather-resistant rubber composition is prepared from the following components in parts by mass: 100 parts of ethylene-vinyl acetate rubber (EVM), 5 to 20 parts of styrene-maleic anhydride copolymer (SMA) and 0.1 to 0.5 part of peroxide. Through ingenious formula design and scientific modification means, the problem of low tensile strength of the EVM is successfully solved, and meanwhile, the excellent weather resistance of the EVM is reserved, so that the EVM has wider application prospects and market potential. The innovative achievement not only provides a new thought and method for modification of the EVM material, but also makes a positive contribution to promotion of technical progress and product upgrading of the rubber industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of synthetic rubber, and specifically relates to a high-strength weather-resistant rubber composition, a masterbatch and a preparation method. Background Art

[0002] Ethylene-vinyl acetate rubber (EVM) is a random copolymer of ethylene and vinyl acetate monomers. When the content of vinyl acetate (VA) in the main chain of the copolymer is between 40wt% and 80wt%, it exists in a rubbery state at room temperature and exhibits unique physical and chemical properties. The unique molecular structure of EVM gives it a series of attractive properties that make it a place in many industrial applications.

[0003] The main chain of EVM's molecule is mainly composed of saturated methylene groups, and this non-polar structure is the fundamental reason for its excellent weather resistance. Compared with rubbers containing unsaturated structures such as butadiene, EVM ages significantly slower, and its tensile strength decrease rate after aging is relatively low. This feature enables EVM to maintain stable performance for a longer time when used outdoors or in harsh environments. In fact, the tensile strength decrease rate of EVM after aging is second only to silicone rubber and fluororubber, two high-performance materials, but it is worth noting that the price of EVM is much lower than that of silicone rubber and fluororubber, which gives it a significant advantage in cost-effectiveness. Therefore, EVM has become a very cost-effective weather-resistant rubber material, especially for those occasions that have strict requirements on the weather resistance of the material but want to control costs.

[0004] In addition to excellent weather resistance, EVM contains ester polar groups on its side chains, which greatly enhances the compatibility of EVM with polar resin systems. This improved compatibility not only makes it easier for EVM to be mixed evenly with other materials during processing, thereby improving the processing performance of the product, but also provides the possibility for the application of EVM in a variety of composite materials. For example, in the manufacture of wires and cables, EVM can be used as an insulating layer or sheath material. Its good compatibility allows the cable to be more closely combined with the core wire or other covering materials during the manufacturing process, improving the overall performance and durability of the cable. In addition, this feature of EVM also makes it widely used in the fields of hoses, adhesives, coatings, plates, and automotive accessories. Especially in the automotive manufacturing industry, EVM is used to manufacture key components such as automotive hoses, seals, and cable sheaths. These components not only need to withstand various mechanical stresses and chemical corrosion during the operation of the car, but also require good sealing and durability. EVM is one of the ideal materials that meet these requirements.

[0005] However, despite its many advantages, EVM also has certain structural shortcomings. Due to the lack of rigid structure in the molecular chain of EVM, its tensile strength is relatively low. This defect limits the use of EVM in certain application fields that have higher requirements for material strength. Summary of the invention

[0006] The present invention aims to overcome at least one defect in the prior art and provide a high-strength weather-resistant rubber composition to solve the problem of insufficient tensile strength of EVM.

[0007] In order to solve the above technical problems, the following technical solutions are adopted:

[0008] In a first aspect, a high-strength weather-resistant rubber composition is provided. The composition, by weight, comprises the following components: 100 parts of ethylene-vinyl acetate rubber (EVM), 5 to 20 parts of styrene-maleic anhydride copolymer (SMA), and 0.1 to 0.5 parts of peroxide.

[0009] Through the scientific proportion and synergistic effect of the above components, the high-strength weather-resistant rubber composition exhibits excellent comprehensive performance. Compared with pure EVM, the modified material has significantly improved tensile strength while maintaining the same weather resistance. This improvement not only broadens the application range of EVM, making it capable of being used in more occasions with strict requirements on mechanical properties, such as automotive seals, building waterproof materials, wire and cable sheaths, etc., but also improves the service life and reliability of the product.

[0010] Preferably, the content of vinyl acetate (VA) in the ethylene-vinyl acetate rubber is 40 to 80 wt%.

[0011] Preferably, the molar ratio of styrene to maleic anhydride in the styrene-maleic anhydride copolymer is (1-4):1.

[0012] Preferably, the peroxide is at least one selected from dicumyl peroxide (DCP), dibenzoyl peroxide (BPO), and di-tert-butyl peroxide (DTBP).

[0013] If necessary, without damaging the original performance, the above composition may also be added with additives commonly used in the field, such as ultraviolet absorbers, antioxidants, flame retardants, fillers, coupling agents, etc.

[0014] In a second aspect, a high-strength weather-resistant rubber masterbatch is provided. The masterbatch is prepared from the high-strength weather-resistant rubber composition.

[0015] Through the scientific proportion and synergistic effect of the components in the high-strength weather-resistant rubber composition, the high-strength weather-resistant rubber masterbatch shows excellent comprehensive performance. Compared with pure EVM, the modified material has significantly improved tensile strength while maintaining the same weather resistance. This improvement not only broadens the application range of EVM, making it capable of being used in more occasions with strict requirements on mechanical properties, such as automotive seals, building waterproof materials, wire and cable sheaths, etc., but also improves the service life and reliability of the product.

[0016] In a third aspect, a method for preparing the above-mentioned high-strength weather-resistant rubber masterbatch is proposed. The method comprises the following steps:

[0017] S1. The ethylene - vinyl acetate rubber, styrene - maleic anhydride copolymer and peroxide are mixed in a ratio to obtain a premix;

[0018] S2. The premix obtained in step S1 is fed into an extruder, and pellets are obtained by extrusion and cutting.

[0019] The high-strength weather-resistant rubber composition can be prepared into a high-strength weather-resistant rubber masterbatch by mixing and extruding granulation. The process is simple, and the mixing and extruding granulation steps can be carried out by conventional processing equipment without the need to modify the equipment, and industrial production can be easily realized.

[0020] Preferably, the ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide in step S1 are put into a high-speed mixer for mixing. More preferably, the temperature of the high-speed mixer is 85-95° C., the rotation speed is 600-700 rpm, and the mixing time is 20-30 min.

[0021] Preferably, the extruder in step S2 is a twin-screw extruder. More preferably, the temperature of the twin-screw extruder from feeding to discharging is set to 180°C, 190°C, 200°C, 220°C, respectively, and the rotation speed is 20-50 rpm.

[0022] Compared with the prior art, this solution has the following beneficial effects:

[0023] Through the scientific ratio and synergistic effect of ethylene-vinyl acetate rubber (EVM), styrene-maleic anhydride copolymer (SMA) and peroxide, the materials prepared by high-strength weather-resistant rubber composition and masterbatch show excellent comprehensive performance. Compared with pure EVM, the modified material has significantly improved tensile strength while maintaining the same weather resistance. This improvement not only broadens the application range of EVM, enabling it to be competent for more occasions with strict requirements on mechanical properties, such as automotive seals, building waterproof materials, wire and cable sheaths, etc., but also improves the service life and reliability of the product. In addition, the material preparation process is simple, and high-strength weather-resistant rubber masterbatch can be made by mixing, granulation, etc., and then the corresponding products can be made by injection molding, etc. The mixing, granulation, injection molding and other processes can be carried out by conventional processing equipment, without the need to modify the equipment, and it is easy to realize industrial production. At the same time, due to the environmental protection and good processing performance of each component, the composition has little impact on the environment during the preparation process, which meets the requirements of sustainable development.

[0024] In summary, this solution successfully solved the problem of low tensile strength of EVM through clever formula design and scientific modification methods, while retaining its excellent weather resistance, making EVM have a wider application prospect and market potential. This innovative achievement not only provides new ideas and methods for the modification of EVM materials, but also makes a positive contribution to promoting technological progress and product upgrading in the rubber industry. DETAILED DESCRIPTION

[0025] This scheme proposes a high-strength weather-resistant rubber composition, masterbatch and preparation method. The high-strength weather-resistant rubber composition includes the following components by mass: 100 parts of ethylene-vinyl acetate rubber (EVM), 5 to 20 parts of styrene-maleic anhydride copolymer (SMA), and 0.1 to 0.5 parts of peroxide. Among them, the content of vinyl acetate (VA) in ethylene-vinyl acetate rubber (EVM) is preferably 40 to 80wt%, the molar ratio of styrene to maleic anhydride in styrene-maleic anhydride copolymer (SMA) is preferably (1 to 4): 1, and the peroxide is preferably at least one of diisopropylbenzene peroxide (DCP), dibenzoyl peroxide (BPO), and di-tert-butyl peroxide (DTBP).

[0026] The high-strength weather-resistant rubber masterbatch is prepared from a high-strength weather-resistant rubber composition, and the preparation process preferably includes the following steps:

[0027] S1. Ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide are put into a high-speed mixer according to the proportion and mixed for 20 to 30 minutes to obtain a premix, wherein the temperature of the high-speed mixer is 85 to 95° C. and the rotation speed is 600 to 700 rpm.

[0028] S2. Feed the premix obtained in step S1 into a twin-screw extruder, and obtain pellets by extrusion and cutting. The temperature of the twin-screw extruder from feeding to discharging is set to 180°C, 190°C, 200°C, and 220°C, respectively, and the rotation speed is 20-50rpm.

[0029] In order to allow those skilled in the art to better understand this solution, the solution is further described in detail below in conjunction with specific examples. The process methods used in the examples are all conventional methods unless otherwise specified; the materials used are all commercially available unless otherwise specified.

[0030] EVM-1 (EVM with 60% VA content): LEVAMELT 600 from LANXESS, Germany;

[0031] EVM-2 (EVM with VA content of 80%): ARLANXEO LEVAPREN 800;

[0032] EVM-3 (EVM with 40% VA content): ARLANXEO LEVAPREN 400;

[0033] SMA-1 (SMA with n(styrene): n(maleic anhydride) = 2:1): Sartomer SMA2000P;

[0034] SMA-2 (SMA with n(styrene): n(maleic anhydride) = 3:1): Crayville SMA3000P;

[0035] SMA-3 (SMA with n(styrene): n(maleic anhydride) = 1:1): Crayville SMA1000P;

[0036] SMA-4 (SMA with n(styrene): n(maleic anhydride) = 4:1): SMAEF40 from Yingmei Technology;

[0037] DCP: CAS#:80-43-3;

[0038] BPO:CAS#:94-36-0;

[0039] DTBP:CAS#:110-05-4.

[0040] Example 1

[0041] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0042] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0043] Example 2

[0044] By weight, 100 parts of EVM-2, 10 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0045] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0046] Example 3

[0047] By weight, 100 parts of EVM-1, 10 parts of SMA-2, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0048] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0049] Example 4

[0050] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 0.2 parts of DCP were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0051] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0052] Example 5

[0053] By weight, 100 parts of EVM-1, 5 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0054] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0055] Example 6

[0056] By weight, 100 parts of EVM-1, 20 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0057] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0058] Example 7

[0059] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 0.1 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0060] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0061] Example 8

[0062] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 0.5 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0063] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0064] Example 9

[0065] By weight, 100 parts of EVM-3, 10 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0066] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0067] Example 10

[0068] By weight, 100 parts of EVM-1, 10 parts of SMA-3, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0069] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0070] Embodiment 11

[0071] By weight, 100 parts of EVM-1, 10 parts of SMA-4, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0072] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0073] Example 12

[0074] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 0.2 parts of DTBP were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0075] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0076] Comparative Example 1

[0077] By weight, 100 parts of EVM-1 and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0078] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0079] Comparative Example 2

[0080] By weight, 100 parts of EVM-1, 30 parts of SMA-1, and 0.2 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0081] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0082] Comparative Example 3

[0083] By weight, 100 parts of EVM-1 and 10 parts of SMA-1 were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0084] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0085] Comparative Example 4

[0086] By weight, 100 parts of EVM-1, 10 parts of SMA-1, and 1.0 parts of BPO were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0087] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0088] Comparative Example 5

[0089] 100 parts of EVM-1 were put into a high-speed mixer and mixed for 25 minutes. The temperature of the high-speed mixer was 90°C and the speed was 700 rpm to obtain a premix. The premix was fed into a twin-screw extruder. The temperature of the twin-screw extruder from feeding to discharging was set to 180°C, 190°C, 200°C, and 220°C, respectively, and the speed was 30 rpm. The pellets were obtained by extrusion and cutting.

[0090] The above pellets were fed into an injection molding machine to prepare the specimens that meet the "1A type" in Section 11 of the tensile test standard "GB / T 1040.2-2018". The specimens were divided into two groups, one group was directly subjected to the tensile strength test according to the standard "GB / T 1040.2-2018", and the other group was first subjected to 28 cycles of aging test according to "Method A, Cycle No. 4" in Table 4 of the standard "ISO 4892-3", and then subjected to the tensile strength test according to the standard "GB / T 1040.2-2018". The test results are shown in Table 2.

[0091] Table 1 Ingredients and dosages of Examples 1 to 12 and Comparative Examples 1 to 5

[0092] EVM-1 EVM-2 EVM-3 SMA-1 SMA-2 SMA-3 SMA-4 DCP BPO DTBP Example 1 100 -- -- 10 -- -- -- -- 0.2 -- Example 2 -- 100 -- 10 -- -- -- -- 0.2 -- Example 3 100 -- -- -- 10 -- -- -- 0.2 -- Example 4 100 -- -- 10 -- -- -- 0.2 -- -- Example 5 100 -- -- 5 -- -- -- -- 0.2 -- Example 6 100 -- -- 20 -- -- -- -- 0.2 -- Example 7 100 -- -- 10 -- -- -- -- 0.1 -- Example 8 100 -- -- 10 -- -- -- -- 0.5 -- Example 9 -- -- 100 10 -- -- -- -- 0.2 -- Example 10 100 -- -- -- -- 10 -- -- 0.2 -- Embodiment 11 100 -- -- -- -- -- 10 -- 0.2 -- Example 12 100 -- -- 10 -- -- -- -- -- 0.2 Comparative Example 1 100 -- -- 0 -- -- -- -- 0.2 -- Comparative Example 2 100 -- -- 30 -- -- -- -- 0.2 -- Comparative Example 3 100 -- -- 10 -- -- -- -- 0 -- Comparative Example 4 100 -- -- 10 -- -- -- -- 1.0 -- Comparative Example 5 100 -- -- 0 -- -- -- -- 0 --

[0093] Table 2 Test results of Examples 1 to 12 and Comparative Examples 1 to 5

[0094] Tensile strength / MPa Tensile strength after aging / MPa Tensile strength decrease rate after aging / % Example 1 42.6 39.8 6.42 Example 2 44.2 41.2 6.72 Example 3 45.7 43.1 5.64 Example 4 41.4 38.9 5.95 Example 5 36.8 34.9 5.23 Example 6 48.1 44.8 6.79 Example 7 38.2 35.9 6.02 Example 8 43.3 40.6 6.23 Example 9 39.5 36.8 6.83 Example 10 44.5 41.9 5.84 Embodiment 11 43.7 41.6 4.80 Example 12 43.3 40.4 6.70 Comparative Example 1 13.2 12.9 2.27 Comparative Example 2 52.3 28.7 45.1 Comparative Example 3 9.4 7.6 19.1 Comparative Example 4 49.2 31.8 35.4 Comparative Example 5 7.8 7.4 5.1

[0095] It can be seen from Table 2 that the rubber masterbatch made of the rubber composition proposed in this scheme has better comprehensive performance. Specifically, the tensile strength of the tensile test specimens supported by the rubber masterbatch of each embodiment can reach more than 36MPa, the tensile strength after aging is still more than 34MPa, and the tensile strength decrease rate after aging is less than 7%. Among them, the decrease rate of tensile strength after aging is not much different from the decrease rate of tensile strength after aging of pure EVM (Comparative Example 5), indicating that the use of SMA and peroxide does not basically damage the weather resistance of EVM itself.

[0096] Compared with Example 1, Comparative Example 1 did not add SMA, and the tensile strength decreased significantly before and after aging. Comparative Example 2 added SMA exceeding the upper limit, and the tensile strength decreased significantly after aging, and the decrease rate of tensile strength after aging exceeded 45%. Comparative Example 3 did not add peroxide, EVM and SMA were difficult to combine, and the tensile strength decreased significantly before and after aging. Comparative Example 4 added peroxide exceeding the upper limit, and the residual peroxide affected the weather resistance, and the tensile strength decreased significantly after aging, and the decrease rate of tensile strength after aging exceeded 35%. Comparative Example 5 only used EVM, and the tensile strength before and after aging was very low.

[0097] In summary, this solution significantly improves the tensile strength of EVM by synergizing SMA and peroxide. Using SMA or peroxide alone cannot significantly improve the tensile strength of EVM. Compared with the prior art, the composition provided by this solution significantly improves the tensile strength of EVM without substantially damaging the weather resistance, thereby obtaining a high-strength weather-resistant rubber masterbatch.

[0098] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A high-strength weather-resistant rubber composition, characterized in that: The composition comprises the following components in parts by mass: 100 parts of ethylene vinyl acetate rubber, 5 to 20 parts of styrene-maleic anhydride copolymer, and 0.1 to 0.5 parts of peroxide.

2. The high-strength weather-resistant rubber composition according to claim 1, characterized in that: The content of vinyl acetate in the ethylene-vinyl acetate rubber is 40-80 wt %.

3. The high-strength weather-resistant rubber composition according to claim 1 or 2, characterized in that: The molar ratio of styrene to maleic anhydride in the styrene-maleic anhydride copolymer is (1-4):

1.

4. The high-strength weather-resistant rubber composition according to claim 1 or 2, characterized in that: The peroxide is selected from at least one of dicumyl peroxide, dibenzoyl peroxide and di-tert-butyl peroxide.

5. A high-strength weather-resistant rubber masterbatch prepared from the composition according to any one of claims 1 to 4.

6. A method for preparing the high-strength weather-resistant rubber masterbatch as claimed in claim 5, characterized in that: The method comprises the following steps: S1. The ethylene - vinyl acetate rubber, styrene - maleic anhydride copolymer and peroxide are mixed in a ratio to obtain a premix; S2. The premix obtained in step S1 is fed into an extruder, and pellets are obtained by extrusion and cutting.

7. The method for preparing high-strength weather-resistant rubber masterbatch according to claim 6, characterized in that: In step S1, the ethylene-vinyl acetate rubber, styrene-maleic anhydride copolymer and peroxide are put into a high-speed mixer for mixing.

8. The method for preparing high-strength weather-resistant rubber masterbatch according to claim 7, characterized in that: The temperature of the high-speed mixer is 85-95° C., the rotation speed is 600-700 rpm, and the mixing time is 20-30 min.

9. The method for preparing high-strength weather-resistant rubber masterbatch according to claim 6, characterized in that: In step S2, the extruder is a twin-screw extruder.

10. The method for preparing high-strength weather-resistant rubber masterbatch according to claim 9, characterized in that: The temperatures of the twin-screw extruder from feeding to discharging are set to 180° C., 190° C., 200° C., and 220° C., respectively, and the rotation speed is 20 to 50 rpm.